2020
DOI: 10.1002/ijgo.13261
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in the third trimester and maternal‐perinatal outcome

Abstract: Objective To evaluate maternal and perinatal outcomes in cases of third‐trimester malaria (TTM). Methods A parity‐matched comparative cohort study was carried out between December 1, 2018, and April 30, 2019, in three university teaching hospitals in Yaoundé (Cameroon). Women with and without TTM were followed up till delivery. The variables analyzed included maternal and gestational ages at delivery, the regimen of intermittent preventive treatment, usage of insecticide‐treated net, history of malaria recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…These prospective studies should be carefully designed, as the sociological and religious dimension of Ramadan may also alter maternal behavior to protect the belief that Ramadan has no effect on their offspring. Another promising approach to studying these effects would be enhanced retrospective study designs based on routine data collection comparing Islamic pregnant women during and outside the Ramadan period to reduce the effect of confounding but only under the condition that (Ramadan) fasting is registered in routine care, as other seasonal effects on birth outcomes may still apply such as malaria [ 73 , 74 ] and vitamin D status [ 75 , 76 ]. These types of studies are also needed in order to confirm the results of high quality studies in birth and fetal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These prospective studies should be carefully designed, as the sociological and religious dimension of Ramadan may also alter maternal behavior to protect the belief that Ramadan has no effect on their offspring. Another promising approach to studying these effects would be enhanced retrospective study designs based on routine data collection comparing Islamic pregnant women during and outside the Ramadan period to reduce the effect of confounding but only under the condition that (Ramadan) fasting is registered in routine care, as other seasonal effects on birth outcomes may still apply such as malaria [ 73 , 74 ] and vitamin D status [ 75 , 76 ]. These types of studies are also needed in order to confirm the results of high quality studies in birth and fetal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Malawi showed that earlier infection (before 24 weeks gestation) was associated with a higher risk of preterm delivery (26). In a Cameroon study, pregnant women who experienced MiP during the third trimester were four times more likely to have preterm deliveries (7). Similarly, in areas with low malaria transmission such as Southeast Asia, P. falciparum infection during late pregnancy was also associated with preterm delivery (24).…”
Section: The Link Between Mip Inflammation and Preterm Babiesmentioning
confidence: 99%
“…Of note, the precise mechanisms behind MiPassociated preterm birth and SGA remains unclear. P. falciparum infection can cause inflammation and potentially disrupt the fine immunological balance required to maintain pregnancy to term (5)(6)(7). On the other hand, SGA is often linked to placental insufficiency and there is also substantial evidence to suggest dysregulated placental development in mothers with MiP (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly P. falciparum adheres to placental villi and reduces the placental blood flow to cause birth defects like LBW [2,11,12]. Malaria in pregnancy has many maternal and fetal complications like abortion, still birth, intrauterine growth restriction (IUGR), preterm delivery, LBW, and maternal death [2,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the placenta is affected by several mechanisms such as cellular adhesion, cytokine production, and mononuclear cell infiltration, malaria parasites can cross the placenta and infect the fetus [ 9 , 10 ]. Particularly P. falciparum adheres to placental villi and reduces the placental blood flow to cause birth defects like LBW [ 2 , 11 , 12 ]. Malaria in pregnancy has many maternal and fetal complications like abortion, still birth, intrauterine growth restriction (IUGR), preterm delivery, LBW, and maternal death [ 2 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%